2020
DOI: 10.1007/s10151-020-02212-x
|View full text |Cite|
|
Sign up to set email alerts
|

Use of a new transanal irrigation device for bowel disorder management by patients familiar with the irrigation technique: a prospective, interventional, multicenter pilot study

Abstract: Background The aim of this study was to evaluate the feasibility of transanal irrigation (TAI) with a new medical device incorporating an electric pump, the IryPump®R Set. Methods An interventional, prospective, open-label, non-comparative, multicenter pilot study on TAI was conducted at three French university hospitals. Patients with experience of TAI were enrolled for a 1-month period during which 5 consecutive TAIs were performed using the IryPump®R Set (B.Braun Melsungen AG Melsungen, Germany). The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Passananti et al (2016) found that problems with balloon bursts were reduced after catheter design was altered. Further, electronic systems with digital functions for TAI that improves user-friendliness (Passananti et al, 2016) and pumps that can increase feasibility (Charvier, Bonniaud, Waz, Desprez, & Leroi, 2020) have been developed none of the participants in the studies included in this review had access to such equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Passananti et al (2016) found that problems with balloon bursts were reduced after catheter design was altered. Further, electronic systems with digital functions for TAI that improves user-friendliness (Passananti et al, 2016) and pumps that can increase feasibility (Charvier, Bonniaud, Waz, Desprez, & Leroi, 2020) have been developed none of the participants in the studies included in this review had access to such equipment.…”
Section: Discussionmentioning
confidence: 99%